Hungarian Monitoring, 27 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Sweden would participate in action against Iraq - UN General Secretary's Iraq talks - Gorbachev in talks with Egyptian foreign minister - Meeting between Walesa and the Pope Domestic Affairs: - General debate on the privatization of trade - József Antall travels to Helsinki - Géza Jeszenszky in talks in Prague - Árpád Göncz receives Kuwaiti emirate delegate - Kuwaiti embassy in Hungary closes operations - Statement on cooperation between Hungarian and Swiss governments - Last Soviet military unit leaves Esztergom Economy: - Drought damage in corn production - New Hungarian-American record company Külpolitika: - Svédország részt venne egy Irak elleni akcióban - Az ENSZ főtitkár iraki tárgyalásai - Gorbacsov az egyiptomi külügyminiszterrel tárgyal - Walesa és a pápa találkozója Belpolitika: - Általános vita a kereskedelem privatizációjáról - Antall József Helsinkibe utazik - Prágában tárgyal Jeszenszky Géza - Göncz Árpád fogadta a kuvaiti emír megbízottját - Szünetel a kuvaiti magyar nagykövetség működése - Együttműködési nyilatkozat a magyar és a svájci kormány között - Esztergomból távozik az utolsó szovjet katonai egység Gazdaság: - A kukoricatermesztők aszálykárai - Új magyar-amerikai hanglemezkiadó